Role of crosstalk between endothelial cells and smooth muscle cells in vascular calcification in chronic kidney disease - Zhang, Yu‐Xia (Cell Prolif, 2021)
Chronic kidney disease (CKD) is a severe health problem worldwide, and vascular calcification (VC) contributes substantially to the cardiovascular morbidity and high mortality of CKD. CKD is often accompanied by a variety of pathophysiological states, such as inflammation, oxidative stress, hyperglycaemia, hyperparathyroidism and haemodynamic derangement, that can cause injuries to smooth muscle cells (SMCs) and endothelial cells (ECs) to promote VC. Similar to SMCs, whose role has been widely explored in VC, ECs may contribute to VC via osteochondral transdifferentiation, apoptosis, etc. In addition, given their location in the innermost layer of the blood vessel lumen and preferential reception of various pro‐calcification stimuli, ECs can pass messages to vascular wall cells and communicate with them. Crosstalk between ECs and SMCs via cytokines through a paracrine mechanism, extracellular vesicles, miRNAs and myoendothelial gap junctions also plays a role in VC. In this review, we emphasize the role of intercellular crosstalk between ECs and SMCs in VC associated with CKD.